Constraints on tree seedling establishment after fires: passing the germination bottlenecks - Macedo, M. A. [UNESP]; Pinhate, S. B.; Bowen, E. C.; Musso, C.; Miranda, H. S. (Wiley, 2022)
Persistence and colonization by tree species in an environment following a fire depends on the effects on seed germination and seedling development. We used seeds of Kielmeyera coriacea and Qualea parviflora as a model to test the effects of high temperatures on germination and initial development of tree seedlings. We exposed the seeds to heat flow (70, 100, 130, 150 or 170 °C) for 2 or 5 min and compared the germination with that of unheated seeds (control). Seedlings were then harvested after 3, 7 or 15 days to evaluate aerial and root mass, root:shoot ratio, presence of cotyledon opening, true leaves, and secondary roots. We found no effect on germination for seeds exposed to temperatures ≥150 °C. However, germination was significantly reduced for seeds exposed to 100 °C for both 2 and 5 min. The mass of 15-day-old K. coriacea seedlings was smaller when seeds were heated at 70 °C for 5 min or at temperatures higher or equal to 100 °C. Qualea parviflora seedlings did not show any difference in mass, but there were marginal differences in the presence of roots and the opening of cotyledons. Kielmeyera coriacea seedlings allocated biomass faster than Q. parviflora. High temperatures affect both quantity and quality of germinable seeds, as well as biomass allocation during initial seedling development. These factors may explain the decrease in seedlings observed after fire, suggesting a bottleneck effect that influences population dynamics and species persistence in systems with frequent fires.
Keywords: Cotyledons; germination; heat shock; savanna; secondary roots; seed mass; seedling growth